Triethanolamine borate as bifunctional Lewis pair catalyst for the cycloaddition of CO2 with epoxides. (March 2022) - Ge, Yuansheng; Cheng, Guoe; Ke, Hanzhong
Graphical abstract: Highlights: Triethanolamine borate (TEOAB) was as efficient bifunctional catalyst for the cycloaddition of CO2 with epoxides. Most cyclic carbonates can be obtained in quantitative yields and high selectivity (99 %). The catalyst can be easily separated from the product by water washing. Abstract: Triethanolamine borate (TEOAB) possessing Lewis pair is an environmentally friendly, nontoxic, cheap and water-soluble catalyst for the cycloaddition of CO2 with epoxides under solvent-free condition. Due to the synergistic effect of Lewis pair, TEOAB exhibits excellent catalytic activity and selectivity (99 %). The catalytic activity can be further improved by using TBAB as co-catalyst. Most cyclic carbonates can be obtained in quantitative yields and can be purified by water washing.